Biology : the science of life - 4 0 16; Greulach, Victor A.;Chiappetta, Vincent J.; 5 (Morristown, N.J. : General Learning Press, 1977)
A textbook whose five main sections are organized around major life functions and the structures that serve them.
A Leogryph book.;Includes index.
Keywords: 2 -- 0; 6; Juvenile literature. -- Biology;Biology. -- 20; 20; 2